Application of Ultrasound Combined with Magnetic Resonance Imaging in the Diagnosis and Grading of Patients with Prenatal Placenta Accreta. (22nd July 2022) - Zhang, Xiaoyan; Liu, Fengfeng; Wang, Xiaoyan
Abstract : In order to study the clinical application value of placenta accreta (PIA) diagnosis and grading, the authors propose a method based on ultrasound combined with magnetic resonance imaging in the diagnosis and grading of prenatal placenta accreta patients. This method is adopted in materials and methods: a retrospective analysis of hospital patients with high suspicion of placenta accreta by clinical or ultrasonography between October 2019 and October 2021, the imaging and clinical data of 312 patients who underwent placental MRI examination. The MRI imaging data of all patients were jointly analyzed, and the main observation indicators are as follows: (1) dark zone in the placenta, (2) disruption of the border of the myometrium, (3) disruption of the myometrium, (4) abnormal blood vessels in the placenta, (5) enlargement of the lower part of the uterus, and (6) local bulge of the bladder/or invasion of the adjacent tissues of the uterus. The results show the following: in MRI combined with ultrasonography (P < 0.05 ), there was no statistical significance in the specificity and accuracy of MRI combined with ultrasound to diagnose PIA (P > 0.05 ). The comparison of graded diagnostic accuracy showed that in ultrasound alone < MRI   alone < MRI combined with ultrasound, the differences were statistically significant (P < 0.05 ). Ultrasound combined with MRI in the diagnosis of placenta accreta is in good agreement with the clinical and surgical pathological results; MRI examination can be used as an important method for prenatal placenta accreta screening. MRI can classify placenta accreta to some extent.